WEBSITE LAYANAN KONSULTASI BKPSDM KABUPATEN BADUNG - Kadek Yuni Suratri; I Gede Santi Astawa; I Putu Gede Hendra Suputra (Jurnal Pengabdian Informatika, 2026)
The Badung Regency Personnel and Human Resources Development Agency (BKPSDM) is a local government agency that has the responsibility of managing and developing human resources, especially the state civil apparatus (ASN) working within the Badung Regency Government. In carrying out its duties, BKPSDM Badung Regency provides services related to personnel administration and development, one of which is consultation that can be carried out by the community and ASN personnel. Society or ASN personnel can consult related to TAPERA, salary increases, management of retirement decision letters (SK), registration of Civil Servant Candidates (CPNS), and other administrative problems. However, the increase in public visits to the BKPSDM office in one day can be an obstacle. Therefore, a consultation service system is needed that allows the community or ASN personnel to submit and monitor consultations without having to come directly to the Badung Regency BKPSDM office and the ASN on duty can also verify efficiently.